Stomatal density and distribution in leaves of Gossypium sp - Silva, Luiz Carlos; Costa, José Tarciso Alves da; Alves, José Ferreira (Pesquisa Agropecuaria Brasileira, 2014)
Stomatal density and distribution in leaves from different varieties of cotton were studied in an experiment conducted at the "Centro de Ciências Agrárias da Universidade Federal do Ceará", Fortaleza, CE, Brazil, during the year of 1951. The experiment was carried out with the following plant materials Herbáceo cv. BR-1 (Gossypium hirsutum L r. latifolium Hutch.); Mocó cv. Veludo C-71 (G. hirsutum L r. marie-galante Hutch.); Verdão, regionally denominated Rasga-letra (G. hirsutum L. r. marie-galante Hutch.). Cotton plants from Mocó and Herbáceo types showed a tendency to a higher stomatal density in the basal region than in the middle and apical regions. In the Verdão, Herbáceo and Mocó types the stomatal density on the abaxial face was about two times higher than that on the adaxial face of the leaf. In Verdão type a more uniform stomatal density distribution on both leaf faces was observed when compared to the other types. The stomatal density of the leaf tended to increase from the bottom to the top In the same plant of the Verdão, Herbáceo and Mocó types.